Household Justice in the View of Polygamy Practitioners - Rico Setyo Nugroho; M. Dliya’ Ulami’; Soiful Hadi (CV Projurnal Mitra Publikasi, 2025)
Polygamy is a divine law that was revealed to humans as well as other laws that certainly contain wisdom and goodness in it. However, not a few polygamous households are destroyed due to injustice committed by the husband. This type of research is a qualitative study that examines the views of polygamy practitioners in implementing justice in the household. The method used is in-depth interviews conducted with polygamy practitioners. The results show that the justice demanded by Sharia is justice in terms of clothing, food, shelter, and overnight stays. The results provide useful information and advice for men who are thinking about or already involved in polygamy, stressing the significance of fairness and accountability. Through exploring the real-life experiences of those in polygamous relationships, this research seeks to promote a better comprehension of how equity can be maintained in these situations, overturning stereotypes and promoting more nuanced discussions on the subject.